A CONTRASTIVE ANALYSIS OF ENGLISH AND BUGINESE DECLARATIVE SENTENCES PATTERN - Colle, Andi Tenry Lawangen Aspat (Study Program of English Literature, 2020)
This study aimed at investigating the differences and similarities of sentences pattern in English and Buginese and the approach of this study used namely qualitative, where the contrastive analysis was chosen as the method of the study in comparing and analyzing sentence patterns of both languages. From the analysis, it revealed that the similarities of two languages were: (1) both languages have similar sentences pattern, especially for the verbal simple present tense and verbal and nominal future tense, (2) both languages, have the same elements to construct a sentence (S+V+O). Meanwhile, the differences between both of them were (1) declarative sentence pattern for the nominal simple present tense, and verbal and nominal past tense between two languages is different. (2) There is no such pattern S + Vlinking + Subject Complement in Buginese since Buginese has no verb tobe. (3) In making past sentences in Buginese, it would involve Ergative Pronoun, namely -na, -no, -ni, and their position attached at the end of word pura. Hopefully, these findings can predict the interference would happen during teaching English as a target language with the student who has Buginese as their mother tongue. Furthermore, it is suggested that future researchers could conduct a Buginese language study in different settings, such as pragmatics analysis, morphological system, and phonology system.